Nomenclatural entanglements associated with Racomitrium chlorocarpum (Grimmiaceae) - Bednarek-Ochyra, Halina (Phytotaxa, 2014)
A nomenclatural history of one of the most neglected and misunderstood species Racomitrium chlorocarpum is presented. Valid publication of this species name was incorrectly ascribed to M. Fleischer and R. chlorocarpum of 1904 is merely a younger isonym of R. chlorocarpum Paris of 1897. The species name is lectotypified with a specimen from Tasmania, Australia, deposited in the Hooker herbarium (BM), and an isolectotype is present in the herbarium of W. Mitten (NY). Racomitrium chlorocarpum is a typical representative of the genus Bucklandiella, the largest segregate of the broadly interpreted genus Racomitrium and the relevant transfer to this genus is effected as Bucklandiella chlorocarpa, comb. nov. The diagnostic characters of the species are briefly summarised. This is a hydrophytic species, endemic to Australasia and is known from SE Australia, Tasmania and New Zealand.